A sea anemone-like CuO/Co3O4 composite: an effective catalyst for electrochemical water splitting. Issue 81 (27th August 2015) - Li, Xiumin; Guan, Guoqing; Du, Xiao; Cao, Ji; Hao, Xiaogang; Ma, Xuli; Jagadale, Ajay D.; Abudula, Abuliti
Abstract : A sea anemone-like CuO/Co3 O4 composite with 3D hierarchical structure exhibits excellent performance for water electrolysis at a low overpotential with high stability. Abstract : A facile unipolar pulse electrodeposition combined with the thermal oxidation method was applied for fabrication of CuO/Co3 O4 composites on carbon electrode for water electrolysis, and it was found that the sea anemone-like one with a 3D hierarchical structure formed at −0.8 V exhibited excellent performance for water electrolysis at a low overpotential with high stability.